2017
DOI: 10.1080/09168451.2017.1300518
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of a PA14 domain-containing galactofuranose-specific β-d-galactofuranosidase from Streptomyces sp.

Abstract: As a constituent of polysaccharides and glycoconjugates, β-d-galactofuranose (Galf) exists in several pathogenic microorganisms. Although we recently identified a β-d-galactofuranosidase (Galf-ase) gene, ORF1110, in the Streptomyces strain JHA19, very little is known about the Galf-ase gene. Here, we characterized a strain, named JHA26, in the culture supernatant of which exhibited Galf-ase activity for 4-nitrophenyl β-d-galactofuranoside (pNP-β-d-Galf) as a substrate. Draft genome sequencing of the JHA26 stra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 26 publications
1
7
0
Order By: Relevance
“…However, we found that the AbfB domain of ORF1110 was dispensable for the Gal f -ase activity of both substrates of artificial p NP-β- d -Gal f and natural Aspergillus fumigatus galactomannan ( 8 ). In contrast, we found that the PA14 domain of ORF0643 was important for the Gal f -ase activity of A. fumigatus galactomannan ( 9 ). We have also found that there are two types of Gal f -ases among the Actinobacteria : one type containing the AbfB domain and the other type containing the PA14 domain ( 9 ).…”
Section: Genome Announcementmentioning
confidence: 72%
“…However, we found that the AbfB domain of ORF1110 was dispensable for the Gal f -ase activity of both substrates of artificial p NP-β- d -Gal f and natural Aspergillus fumigatus galactomannan ( 8 ). In contrast, we found that the PA14 domain of ORF0643 was important for the Gal f -ase activity of A. fumigatus galactomannan ( 9 ). We have also found that there are two types of Gal f -ases among the Actinobacteria : one type containing the AbfB domain and the other type containing the PA14 domain ( 9 ).…”
Section: Genome Announcementmentioning
confidence: 72%
“…Another Galf -ase gene was also found later in the genome of Streptomyces sp., strain JHA26, coding for 869 amino acids. The Galf -ase specific enzyme was expressed, purified and characterized with the highest activity at pH 4.5 and temperature stability up to 45 • C and with K M of 6.8 mM for pNP-β-d-Galf as a substrate [65,66]. The most recent addition of cloned enzymes is the one from 2019, which provided the complete biochemical and kinetic characterization of subcloned Streptomyces spp.…”
Section: Galactofuranosidasesmentioning
confidence: 99%
“…This enzymatic activity has been observed and monitored in various microorganism species for decades, [15][16][17][18] but proteins responsible for these activities were never isolated until recently. 19,20 Even so, the recently cloned galactofuranosidases have quite low activities (K M values of 4.4-6.8 mM, no reported k cat values) and have only been characterized in hydrolysis mode of either the natural Aspergillus fumigatus galactomannan or the non-natural substrate p-nitrophenyl-β-D-galactofuranoside 1 so their potential as a synthesis tool has not been demonstrated. Fortunately, β-D-galactofuranose and α-L-arabinofuranose are closely related glycosides, their only difference being an additional hydroxymethyl group on the C-5 of galactofuranose compared to arabinofuranose (Figure 1), so we supposed that enzymes acting on L-arabinofuranose might also have an activity against D-galactofuranose, or at least could be a starting point for the development of a biocatalyst using galactofuranose as substrate.…”
Section: -9mentioning
confidence: 99%